A thermally self-sustaining solid oxide fuel cell system at ultra-low operating temperature (319 °C). (1st June 2016) - Chang, Ikwhang; Bae, Jiwoong; Park, Joonho; Lee, Sunho; Ban, Myeongseok; Park, Taehyun; Lee, Yoon Ho; Song, Han Ho; Kim, Young-Beom; Cha, Suk Won
Abstract: A thermally stable and self-sustainable portable energy conversion system is designed using low temperature thin film SOFCs (solid oxide fuel cells). Hydrogen and air gases are fed into this system, which is successfully operated at 319 °C. Each cell, comprised of Pt (anode)/YSZ-GDC-YSZ/Pt (cathode), is manufactured using sputtering and atomic layer deposition, and the area of a single cell is 2.56 cm 2 . The maximum absolute power and power densities at 500 °C are measured to be 44 mW and 17 mW cm −2, respectively. To the best of our knowledge, this represents the highest absolute power reported at such a low operating temperature regime. To increase the system's temperature, a catalytic burner using Al2 O3 and a Pt catalyst is manufactured by dip-coating. After hydrogen gas and air pass through the anode and cathode sides, respectively, the mixed fuel gases are supplied to the catalytic burner, which undergoes an exothermic reaction. We successfully demonstrate that this system is heated up to 319 °C (from room temperature) without any other initial heat source; we also measure the electrical power simultaneously. Highlights: An energy system using thin film SOFCs (solid oxide fuel cells) is successfully demonstrated. The energy system is highly thermally stable and self-sustained at 319 °C. An OCV (open circuit voltage) of 3 V and a maximum power density of 0.6 mW at 319 °C are achieved. We fabricate a single SOFC cell with active area of 2.56 cm 2 .